MENINGKATKAN MINAT BELAJAR MATERI PENDIDIKAN AGAMA KATOLIK MELALUI APLIKASI CANVA - Sabon, Elisabeth Susilia Liwa; Keban, Yosep Belen; Aran, Alfonsus Mudi (Bahasa Indonesia, 2025)
Education in the 21st century demands that both students and educators adapt to the evolving needs of modern times. However, many teachers have struggled to incorporate technology into their teaching practices, which negatively affects students' motivation to learn. As a result, it is essential for teachers to integrate contemporary technology into the learning process. One such tool is the Canva application, which can be used effectively in education. This study aimed to explore the use of Canva as a learning medium for Catholic Religious Education (PAK) and assess its impact on enhancing the learning interest of eighth-grade students at SMPK Sanctissima Trinitas Hokeng. The research employed a qualitative descriptive approach, using interviews, observations, and documentation as data collection methods. The study involved 8 informants: 6 eighth-grade students, 1 PAK teacher, and the principal. The findings revealed that Canva's use as a PAK learning tool at SMPK Sanctissima Trinitas Hokeng successfully increased students' interest in learning, thanks to its engaging design, interactive features, and diverse display options.